Parental feeding practices and parental involvement in child feeding in Denmark: Gender differences and predictors. (1st March 2022) - Philippe, Kaat; Chabanet, Claire; Issanchou, Sylvie; Grønhøj, Alice; Aschemann-Witzel, Jessica; Monnery-Patris, Sandrine
Abstract: Studies about fathers and feeding are scarce and little is known about predictors of parental involvement in child feeding and of paternal feeding practices. Therefore, this study aimed to examine possible differences between Danish mothers and fathers with regard to their feeding practices and involvement in feeding related tasks, and to assess possible parent-related predictors of parental practices and involvement. A total of 261 mothers and 321 fathers of pre-schoolers completed an online survey with items from validated questionnaires. Gender differences were observed; fathers reported using higher levels of coercive control practices, while mothers reported using higher levels of structure practices and autonomy support practices. Both mothers and fathers reported to be highly involved in feeding their child. Regressions showed that a higher concern for child weight and a higher motivation for child preference when buying food were linked to a higher use of coercive control practices while a higher motivation for health control when buying food, cooking confidence, feeding/general self-efficacy and perceived responsibility for feeding were linked to a higher use of structure and autonomy support practices. The results of this study provide valuable insight into maternal and paternal practices in Denmark and their determinants.